Does fesoterodine have a role in the treatment of poorly managed patients with overactive bladder? - Morris V; Wagg A (Dove Medical Press, 2014)
Vikky Morris,1 Adrian Wagg21Geriatric Medicine, Taunton Hospital Somerset, UK; 2Division of Geriatric Medicine, University of Alberta, Edmonton, Alberta, CanadaAbstract: Overactive bladder (OAB), a clinically defined symptom complex comprising urinary urgency, usually accompanied by urinary frequency and nocturia, with or without urgency incontinence, is common and has a markedly negative impact on the sufferer's quality of life. Following conservative and lifestyle management, the current pharmacological mainstay of treatment is antimuscarinic therapy. This review explores the role of fesoterodine, a relatively recently introduced antimuscarinic agent, in the treatment of patients who may have had a suboptimal response to initial therapy, who have switched treatment from tolterodine, or may be at risk of receiving poor treatment because of either multimorbidity or complex polypharmacy.Keywords: elderly, fesoterodine, overactive bladder, urgency incontinence